Oncocytoma of the Submandibular Gland: Diagnosis and Treatment Based on Clinicopathology - Betty Chen; Joshua I. Hentzelman; Ronald J. Walker; Jin-Ping Lai (Case Reports in Otolaryngology)
Background. Submandibular oncocytomas are rare benign salivary gland neoplasms. They are typically found in Caucasian patients aged 50–70 years with no gender preference. Due to the overlapping histological and clinical features of head and neck tumors, they are often misdiagnosed. Methods. We report a case of unilateral submandibular gland oncocytoma in a 63-year-old Caucasian man. Results. The patient underwent unilateral submandibular gland resection and histopathologic analysis of the tumor specimen. On follow-up at 2 weeks and 1 year, no recurrence was identified. Conclusion. Submandibular oncocytomas are best diagnosed with preoperative FNA and CT imaging and have distinctive findings on cytology and histology. CT followed by fine-needle aspiration cytology would be the preferred diagnostic modalities. Due to its low rate of malignant transformation and recurrence, the best treatment is local resection with follow-up as necessary.